After the accord : a history of Federal Reserve open market operations, the US government securities market, and Treasury debt management from 1951 to 1979 - Garbade, Kenneth D. (Cambridge : Cambridge University Press, 2021)
In this book Garbade, a former analyst at a primary dealer and researcher at the Federal Reserve Bank of New York, traces the evolution of open market operations, Treasury debt management, and the microstructure of the US government securities markets following the 1951 Treasury-Federal Reserve. This volume examines how these operations evolved, responding both to external forces and to one another. Utilising a vast scope of primary material, the work provides insight into how officials fashioned the instruments, facilities, and procedures needed to advance their policy objectives in light of their novel freedoms and responsibilities. Students and scholars of macroeconomics, financial regulation, and the history of central banking and the Federal Reserve will find this volume a welcome addition to Garbade's earlier studies of Treasury debt operations during World War I, the 1920s, and the Great Depression and since 1983.
Title from publisher's bibliographic system (viewed on 15 Jan 2021).
Keywords: United States. -- Federal Reserve Board; United States. -- Department of the Treasury; Open market operations -- United States -- History -- 20th century; Government securities -- United States -- History -- 20th century; Finance -- Government policy -- United States -- History -- 20th century; Monetary policy -- United States -- History -- 20th century